Spatial Apparent Electrical Conductivity of Paddy Soil as an Indicator of Rice Productivity - Chan, Chee Sheng (2006)
Paddy soils are naturally heterogeneous in terms of their physico-chemical properties which influence rice productivity. Currently, uniform application of agricultural fertilizers for the entire field is not efficient and could result in either insufficient or excess nutrient supply. Good agricultural practices can be achieved if soil and nutrient variations within a farm are considered, and a soil-yield interrelationship is established. Simple, rapid and accurate methods to characterize variation in soil properties are needed.